Identifying Barriers to Municipal Climate Neutrality: Case Study of Latvia (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2026)
Local governments play a key role in achieving climate neutrality goals, as the local level is where measures are implemented in the areas of energy management, mobility, territorial development and public services, which directly affect greenhouse gas emissions. The competence of local governments is broad, and although the impact of climate change is evident and the integration of climate goals into regulatory framework is increasing, the prioritization of these topics is not always prominent on the agenda of local governments. However, local government action in the field of emission reduction is often limited by various structural, institutional and practical barriers, the significance and impact of which can vary significantly depending on the local context. This study focuses on the experiences and perspectives of Latvian municipalities on the barriers to achieving climate neutrality, based on the results of a survey of municipalities. The survey serves as the main empirical basis for identifying barriers, assessing their significance and comparing them. The responses provided by municipal representatives allow us to assess which barriers most hinder the implementation of emission reduction measures in practice, as well as to reveal differences between municipalities of different sizes and capacities. The survey results are analyzed in conjunction with existing research on energy management and climate policy implementation in European municipalities, thus providing both an empirical and analytical perspective on the problem. The analytical approach has resulted in conclusions and practical recommendations based on the real needs of local governments, aimed at more effective emission reduction and achieving climate neutrality goals at the local level. The broad scope and mutual influence of barriers shows that transition to climate neutrality is an interdisciplinary issue, in which local governments must be able to apply an integrated approach. At the same time, the results of the study highlight different and divergent experiences of how climate issues are prioritized in local governments, both at the political and management levels – often the prioritization of climate issues among other issues within the competence of a local government is related to the capacity, size and financial capabilities of the local government.